Revised nomenclature of the sea pen genus Balticina Gray, 1870 (= Halipteris Kölliker, 1870) (Anthozoa: Octocorallia) - Pérez, Carlos Daniel; Cordeiro, Ralf Tarciso Silva; Williams, Gary C.; Gomes, Paula Braga (Zootaxa, 2021)
The pennatulacean genus Balticina has had a long and confusing taxonomic history, with serious nomenclatural problems that remain unresolved. Owing to disagreements about authorships and dates of publication, the names Pavonaria, Norticina and Halipteris have all been used as valid in place of Balticina, or else been regarded as its junior synonyms, even simultaneously. In this paper, after an extensive literature review, we determine the authorships and dates for all the taxa involved in accordance with the provisions of the International Code of Zoological Nomenclature and establish Balticina Gray, 1870 (=Halipteris) and Balticinidae Balss, 1910 (=Halipteridae) as the valid genus and family names, respectively, for this group of sea pens. We also propose the replacement name Rakollikeria for the preoccupied genus name Pavonaria Kölliker, 1870 (Balticinidae) (nec Schweigger, 1819 - Funiculinidae).